Violence Victimization, Social Support, and Papanicolaou Smear Outcomes: A Longitudinal Study from Adolescence to Young Adulthood - Hsieh, Hsing-Fang (J Womens Health (Larchmt), 2017)
Background: African American youth are among those at greatest risk for experiencing violence victimization. Notably, the mortality rate of cervical cancer for African American women is also twice that of white women. To date, we know of no literature using longitudinal data to examine how violence victimization relates to Papanicolaou (Pap) smear results or cervical cancer in this population. Our study examines how violence victimization during adolescence (age 15 to 18) influences psychological distress, perceived social support, heavy substance abuse, and sexual risk behaviors during emerging adulthood (age 20 to 23), and subsequent Pap smear outcomes during young adulthood (age 29 to 32). Method: This study is based on 12 waves of data collected in a longitudinal study of 360 African American women from mid-adolescence (ninth grade, mean age = 14.8 years) to young adulthood (mean age = 32.0 years). We used structural equation modeling analysis to examine the hypothesized model. Result: Violence victimization during adolescence had a direct effect on decreased social support, increased psychological distress, and increased heavy cigarette use during emerging adulthood. Better social support was also associated with fewer sexual partners during emerging adulthood and lower odds of abnormal Pap smear results during young adulthood. The effect of violence victimization on abnormal Pap smear was mediated by social support. Conclusion: Our results show that violence victimization during adolescence has long-term negative effects through multiple pathways that persist into adulthood. Our findings also suggest that social support may help to compensate against other risk factors. Interventions designed to address the perceived support may help victims cope with their experience.